2015
DOI: 10.1039/c5tc01915j
|View full text |Cite
|
Sign up to set email alerts
|

DNA-mediated control of Au shell nanostructure and controlled intra-nanogap for a highly sensitive and broad plasmonic response range

Abstract: We report DNA-mediated simple synthetic methods to obtain anisotropic plasmonic nanostructures with a tailorable intra-nanogap distance ranging from 0.9 to 4.0 nm. Anisotropic half-shell structures with sub-1.0 nm intra-nanogaps showed a wavelength-independent surface-enhanced Raman scattering (SERS) intensity and a highly sensitive SERS response to NIR light. We found that the reaction conditions such as pH and NaCl concentration are responsible for the resulting shell structures and intra-nanogap distances. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Recently, novel nanoprobes called “SERS tags”, consisting of silver or gold nanostructures and specific Raman reporter molecules, have been synthesized to develop SERS-based biological analyses. Despite the ultrasensitive, multiplex, and biocompatible properties of SERS tags, challenges are often encountered in the complex and delicate synthetic steps, as well as practical use . More recent research has led to the synthesis of well-defined gold nanobridged nanogap particles (Au-NNPs) for stable, highly quantitative, and controllable SERS enhancement. The existence of interior nanogaps in nanostructures holds great promise for developing universal SERS nanotags and multiplex nanoprobes. However, several critical techniques still remain challenging, including simple and controllable synthesis of Au-NNPs, modification of the interior nanogap of nanotags with Raman reporters to produce intense and stable multiplex SERS signals, and functionalization of the nanotags as SERS nanoprobes to recognize different bioactive molecules.…”
mentioning
confidence: 99%
“…Recently, novel nanoprobes called “SERS tags”, consisting of silver or gold nanostructures and specific Raman reporter molecules, have been synthesized to develop SERS-based biological analyses. Despite the ultrasensitive, multiplex, and biocompatible properties of SERS tags, challenges are often encountered in the complex and delicate synthetic steps, as well as practical use . More recent research has led to the synthesis of well-defined gold nanobridged nanogap particles (Au-NNPs) for stable, highly quantitative, and controllable SERS enhancement. The existence of interior nanogaps in nanostructures holds great promise for developing universal SERS nanotags and multiplex nanoprobes. However, several critical techniques still remain challenging, including simple and controllable synthesis of Au-NNPs, modification of the interior nanogap of nanotags with Raman reporters to produce intense and stable multiplex SERS signals, and functionalization of the nanotags as SERS nanoprobes to recognize different bioactive molecules.…”
mentioning
confidence: 99%
“…Perrault et al [ 44 ] reported that rod-shaped nanomaterials have much higher blood circulation half-lives than spherical nanomaterials. Moreover, Lee et al [ 45 ] reported the successful control of gold shell nanostructures such as a star-shaped shell with irregular nanogap and intra-nanogap distances by pH and NaCl concentrations. Accordingly, we attempted to modulate the shape of gold shell nanostructures through modulations of pH to protect the release of radioiodine from gold core nanoparticles by various biological factors in living subjects and effectively enhance passive tumor targeting efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The EM field inside Au-NNP generated by the complete Au shell is stronger and more uniform than that generated by the incomplete one ( Figure 4C3). Similarly, Lee and his co-workers [66] found the reaction parameters such as pH and NaCl concentration, have great influence on the DNA conformation, and thereby they obtained three anisotropic plasmonic nanostructures with different shell structures and adjustable intra-nanogap distance on a nanoscale. It is worth expecting that other materials such as Ag and Pt-NNPs can be synthesized, and then be applied to more scientific and engineering fields.…”
Section: Surfactant or Capping Agentmentioning
confidence: 95%